Politics of folklore in Croatia - Marković, Jelena (Array, 2014)
In this paper the authors analyze the relationship between folklore, folkloristics, ethnology and politics in a broad sense. The history of this relationship starts during the formative period of the disciplines, in the “discovery” of their object of research, and its complex aspects are visible in a whole range of disciplinary themes, omissions, gaps and neuralgic spots (historical, social, cultural, as well as disciplinary). Some of them are addressed in this article, for example, a tendency in folkloristics (and some currents in ethnology) to preserve in the present something that is not completely of the present, the instrumentalization of folklore in the construction of national myths and their utilization as part of political propaganda, the relationship between folklore and folklorism, the role of disciplines in the “institutionalization” of folklore practices within various national and supranational initiatives, or the participation of professionals in marketable “applied” projects as a pragmatic response to new scientific politics of austerity.